The change of stress distribution on the condyle after mandibular setback surgery - Ueki, Koichiro; Nakagawa, Kiyomasa; Takatsuka, Shigeyuki; Yamamoto, Etsuhide (European journal of orthodontics, 2006)
The rigid-body spring model (RBSM) theory was incorporated into a model as a discrete method for analysing problems of limit, such as the stress distribution on the condyle. The purpose of this study was to evaluate the two-dimensional RBSM for determining stress on the temporomandibular joint (TMJ) in patients after orthognathic surgery. Thirty-two patients (five males and 27 females, mean age 21.4 ± 4.9 years) with mandibular prognathism underwent bilateral sagittal split ramus osteotomy (SSRO) and setback; 48 subjects were recruited as controls. Anatomical landmarks were traced from pre- and post-operative lateral cephalograms and the information was processed using the Fortran analysis program. The force vector on the condyle, its degree, its direction, and the displacement co-ordinates (x, y) and rotation (q) at the gonial angle were calculated.  When muscular power was assumed to be 1, the post-operative degree of the force vector was higher than the pre-operative value (P < 0.05). The X co-ordinate, x, and rotation, q, of the displacement vector in the pre-operative patients with mandibular prognathism were significantly higher than those in the control subjects (P < 0.05). There were still significant differences between the displacement values post-operatively between the patients and controls (P < 0.05).  The results suggest that the degree and direction of the force vector and the resulting displacement co-ordinates can be used as parameters in a surgical model. The RBSM may also be useful in evaluating the pre- and post-operative skeletal morphology of jaw deformities.